Environmental, social and corporate governance (ESG) on the financial performance of listed mining firms in South Africa - Dylan Evans; Grace Anna Kramer; Marco Lanfranchi; Pradeep Brijlal (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2023)
Purpose: This study aimed to determine the relationship between the environmental, social, and governance factors (ESG) and the financial performance of mining firms within South Africa. Prior research has focussed primarily on the ESG components and lacked further investigation on the sub-components of ESG as it applies to specific sectors. Design/methodology/approach: Convenience and judgment sampling were used to draw a sample from a publicly available database. Based on a criterion for robust analysis, 13 of 41 JSE listed mining companies were selected. This study used a two-way random effects panel regression analysis to determine the relationship between ESG variables and firm financial performance on JSE- listed mining firms, in South Africa from 2008 to 2020. Findings: There was no statistical relationship between overall ESG score and firm performance. However, only the Governance score illustrated a statistically significant relationship with financial performance. Within the sub-components, the following had a significant negative relationship with firm performance: emissions; environmental innovation; working conditions; and shareholder responsibility. However, human rights and CSR strategy significantly positively correlated with financial performance. Research limitations/implications: This research was conducted specifically on South African mining companies, and therefore cannot be generalised to other industries or markets in developing and developed countries. Managers and policymakers within the mining industry should consider the practical implications and interpretations of the findings and may offer incentives to implement improvements regarding emissions, environmental innovation, and working conditions. Originality/value: This research delved deeper into the sub-components of the ESG pillars to get a better understanding of each sub-component on firm performance.
Keywords: G10; G30; G34; M14; 330; ESG; financial performance; asset utilisation; panel regression